Газодинамічні методи зниження рівня вібронапружень в лопаткових вінцях осьових турбодвигунів - Кірчу, Ф. І.; Терещенко, Ю. М.; Ластівка, І. А.; Кинащук, І. Ф. (Eastern-European Journal of Enterprise Technologies, 2009)
In article the generalised results of researches of influence on level of vibration stress in blade row of axial compressor stage gasdynamic actions on the district periodic non-uniformity of a stream caused by aerodynamic traces behind elements stator are considered